EBS-PBM apps as an innovative digital media for enhancing numeracy skills in learning fractions in elementary school - Isrokatun, I.; Syahid, Aah Ahmad; Hanifah, Nurdinah; Rohman, Yusuf Abdul; Rosmiati, Rosi; Hanum, Citra Bahadur (Edelweiss Applied Science and Technology, 2025)
Numeracy skills, particularly in fractions, are essential foundational competencies for elementary school students, supporting the understanding of more advanced mathematical concepts at subsequent levels. However, various studies have shown that students continue to face difficulties in understanding and performing operations with fractions, due to both cognitive and pedagogical factors. This study aims to describe the design and features of the EBS-PBM Apps as an innovative digital media, as well as to explore students’ perceptions, interests, and challenges encountered during its use, and its impact on enhancing numeracy skills. A quasi-experimental approach was employed using a one-group pretest-posttest design, involving 45 elementary school students in Sumedang Regency, West Java, Indonesia. Data were collected using a questionnaire. The results indicate that the EBS-PBM Application was positively received by students and significantly improved their interest and numeracy skills in fractions. The application was considered engaging, user-friendly, and effective in stimulating students’ counting abilities in an interactive and contextual manner. This study recommends the integration of digital medium such as the EBS-PBM Apps into mathematics instruction to support early mastery of numeracy skills.